Catalytic hydrothermal deoxygenation of lipids and fatty acids to diesel-like hydrocarbons: a review. Issue 3 (3rd February 2021) - Yao, Xiaoyi; Strathmann, Timothy J.; Li, Yalin; Cronmiller, Lauren E.; Ma, Huiling; Zhang, Jing
Abstract : This review summarizes the reactions, catalysts and influence factors in the hydrothermal deoxygenation of lipids and fatty acids to diesel-like hydrocarbons. Abstract : In recent years, due to the depletion of fossil fuels and environmental problems, the use of non-edible lipids ( e.g., waste and microalgal oils) and fatty acids to produce fuels has received much more attention. Most of these lipid materials contain large amounts of water, which makes the hydrothermal process a very attractive method. This review describes the advancements in the preparation of diesel-like hydrocarbons by the deoxygenation of lipid and fatty acid feedstocks under hydrothermal conditions. Firstly, all reactions in the hydrothermal deoxygenation process, e.g. hydrodeoxygenation, decarboxylation, decarbonylation, hydrogenolysis, reforming, etc ., are described. Secondly, the activity, selectivity and stability of various catalysts, mainly metal-based catalysts, are discussed. Thirdly, the influence of reaction conditions, i.e. the amount of catalyst, reaction temperature, reaction atmosphere, feedstocks, water, and reactors, is summarized. Finally, the directions of further study on the production of diesel-like hydrocarbons by hydrothermal deoxygenation are proposed.